2019
DOI: 10.1038/s41598-018-36810-5
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of PREX2 gene in patients with hepatocellular carcinoma

Abstract: Characterized with a high recurrence rate and low detection rate, prevention is the best approach to reduce mortality in hepatocellular carcinoma (HCC). The overexpression of Phosphatidylinositol-3,4,5-Trisphosphate Dependent Rac Exchange Factor 2 (PREX2) is observed in various tumors, including HCC; and the frequent PREX2 mutations in melanoma are associated with invasiveness. We sought to identify somatic mutations and the functional changes in mutational signatures of PREX2. Genomic DNA sequencing was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…Among these identified highly mutated genes, TP53, TERT, PEEX2, CTNNB1, and AXIN1 in HCC, especially in HBV-related HCC, have been investigated, and the published studies showed that these mutated genes played very important roles in the development of HCC. 10,11,18,21 In addition, consistent with the published studies, we found that COL11A1, RB1, MUC16, and PCLO, which have been detected by next-generation sequencing technology, 13,21-23 including whole genome sequencing and whole-exome sequencing by different groups, are also found to be associated with HCC in our research. However, the role of other mutated genes, including ABCA13, COL11A1, and COL12A1 as shown in Figure 2A, in HBV-related HCC, has not been well clarified and needs to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Among these identified highly mutated genes, TP53, TERT, PEEX2, CTNNB1, and AXIN1 in HCC, especially in HBV-related HCC, have been investigated, and the published studies showed that these mutated genes played very important roles in the development of HCC. 10,11,18,21 In addition, consistent with the published studies, we found that COL11A1, RB1, MUC16, and PCLO, which have been detected by next-generation sequencing technology, 13,21-23 including whole genome sequencing and whole-exome sequencing by different groups, are also found to be associated with HCC in our research. However, the role of other mutated genes, including ABCA13, COL11A1, and COL12A1 as shown in Figure 2A, in HBV-related HCC, has not been well clarified and needs to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 91%
“…We identified 78 highly mutated genes that associated with HBV‐related HCC, and the results were further validated by using the LICA‐CN cohort in ICGC database. Among these identified highly mutated genes, TP53, TERT, PEEX2, CTNNB1, and AXIN1 in HCC, especially in HBV‐related HCC, have been investigated, and the published studies showed that these mutated genes played very important roles in the development of HCC . In addition, consistent with the published studies, we found that COL11A1, RB1, MUC16, and PCLO, which have been detected by next‐generation sequencing technology, including whole genome sequencing and whole‐exome sequencing by different groups, are also found to be associated with HCC in our research.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations